High quality audio power amplifier module / Nazaruddin Ibrahim and Azlan Nawi - Ibrahim, Nazaruddin; Nawi, Azlan (1989)
This new amplifier module will produce high power with low distortion. It is small and very compact. It is simple to build and cost far less than other modules with similar power. Amplifier modules often have to operate in rather rigorous condition, pacing both the load and the amplifier itself at risk. The essence of this problem is failure of the output device when their current and voltage relationship exceeds the SOAR curve. The amplifier module has the ability to reject unwanted signal (noise and distortion) at the output where signals are needed.